EVALUATION OF SUITABILITY OF METHODS FOR TESTING BLOOD PROTEIN HYDROLYSATES FOR THEIR BIOLOGICAL ACTIVITY AND TOXICITY - M. N. Guseva; M. I. Doronin; M. A. Shevchenko; D. V. Mikhalishin; A. A. Shishkova (Ветеринария сегодня)
The use of high quality nutrient media comprising protein hydrolysates as the main components for maintaining their nutrient value is a critical prerequisite for appropriate fnal product preparation in FMD vaccine biotechnology. The incoming control of raw materials, in particular testing blood protein hydrolysates of diﬀerent batches for their quality, is of considerable importance. Currently, there are diﬀerent methods for the determination of hydrolysate efcacy using cell cultures and unicellular organisms as test systems. We used suspended baby hamster kidney (ВНК-21) cell line as a model for testing blood protein hydrolysates in the raw materials intended for FMD vaccine production for their biological activity and toxicity. The validation of the proposed method was carried out to confrm the reliability of the test results obtained. The following main validation characteristics were determined through testing 560 blood protein hydrolysate samples: trueness, specifcity, sensitivity, as well as precision under repeatability and reproducibility conditions. The validation results for the proposed method demonstrated high reliability (Fisher’s criterion – 0.021; ≤0.050) and full compliance with acceptance criteria.